2010
DOI: 10.3892/ijmm_00000472
|View full text |Cite
|
Sign up to set email alerts
|

Anti-asthmatic activities in mycelial extract and culture filtrate of Cordyceps sphecocephala J201

Abstract: Abstract. This study investigated the effects of mycelial extract and culture filtrate of Cordyceps sphecocephala J201 on airway hyper-responsiveness, pulmonary immune cell infiltration, and Th2 cytokine expression in animal models of asthma. After Concanavalin A (Con A) activation of mouse primary spleen cells, the IL-4 and IL-13 cytokine expression were significantly decreased in the presence of the mycelial extract and culture filtrate of Cordyceps sphecocephala J201. The asthma model was induced by sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Oral FIP-fve had an anti-inflammatory effect on OVA-induced airway inflammations and might possess a potential for the treatment of an allergic response within the body. Mycelia of Cordyceps sphecocephala extract were injected to assess the effects of anti-asthmatic activity on lung cells of ovalbumin-induced asthmatic mice and the results revealed that increasing levels of IL-4, IL-13 and IL-25 expression were controlled (Heo et al 2010) and reduced immune responses by the inhibition of the expression of cytokine were observed in asthmatic mice.…”
Section: Antiasthmatic Properties Of Mushroomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral FIP-fve had an anti-inflammatory effect on OVA-induced airway inflammations and might possess a potential for the treatment of an allergic response within the body. Mycelia of Cordyceps sphecocephala extract were injected to assess the effects of anti-asthmatic activity on lung cells of ovalbumin-induced asthmatic mice and the results revealed that increasing levels of IL-4, IL-13 and IL-25 expression were controlled (Heo et al 2010) and reduced immune responses by the inhibition of the expression of cytokine were observed in asthmatic mice.…”
Section: Antiasthmatic Properties Of Mushroomsmentioning
confidence: 99%
“…24.2 8.2 -Anti-asthma Heo et al (2010) and Cheung (2010) 14 Phyllanthus ---Anti-viral Yang et al (2005) 15…”
Section: Introductionmentioning
confidence: 99%
“…Natural chemicals obtained from mushrooms can be thoroughly investigated and evaluated, which can be extremely beneficial for treating both infectious and noninfectious disorders [ 7 , 8 ]. Medicinal mushrooms and fungi are believed to have 130 different therapeutic properties, including antiallergic [ 9 ], antiarthritic, antiasthmatic [ 10 ], anticancer [ 11 ], pesticide [ 12 ], antidepressive [ 13 ], antidermatophytic [ 14 ], antidiabetic [ 15 ], antifertility, antifungal [ 15 ], antihelminthic [ 16 ], cytotoxic [ 17 ], antihypercholesterolemic [ 18 ], antihyperlipidemic [ 19 ], antihypertensive [ 20 ], antihypocholesterolemic [ 21 ], anti-inflammatory [ 15 ], antimalarial [ 22 ], antimicrobial [ 15 ], antioxidant [ 11 ], antiparasitic [ 23 ], antispasmodic [ 24 ], antiviral [ 13 ], anticardiovascular illnesses [ 18 ], hepatoprotective [ 10 ], immunomodulator [ 22 ], immunostimulant [ 13 ], insecticidal [ 22 ], larvicidal [ 25 ], nematicide [ 26 ], nephroprotective, neuroprotective [ 13 ], osteoprotective [ 4 ], and vasodilator [ 27 ], among others.…”
Section: Introductionmentioning
confidence: 99%
“…(1868), is an entomopathogenic fungi parasitizing on bees or wasps, belongs to the genus of Ophiocordyceps, the order of Hypocreales, and the family of Clavicipitaceae (Sung et al, 2007). Ophiocordyceps sphecocephala has been potential as a novel therapeutic agent for cancer treatment, anti-asthmatic activities, and so on (Heo et al, 2010;Oh et al, 2008). It is critical to creating procedures for authenticating Ophiocordyceps sphecocephala since species identification is a significant and vital process for controlling the quality and uniformity of herbal medicines.…”
Section: Introductionmentioning
confidence: 99%